2018
DOI: 10.3892/etm.2018.6939
|View full text |Cite
|
Sign up to set email alerts
|

Oligo‑fucoidan improved unbalance the Th1/Th2 and Treg/Th17 ratios in asthmatic patients: An ex vivo study

Abstract: An imbalance in the helper T cells (Th)1/Th2 and regulatory T cells (Tregs)/Th17 ratios is believed to play a key role in asthmatic inflammatory responses. Fucoidan reportedly reduces the production of inflammatory factors. Nutritional intervention is an important tool in decreasing the severity of asthmatic disease. This study aimed to investigate the beneficial roles of oligo-fucoidan in balancing the T cell subtype ratios and reducing airway inflammation ex vivo. Peripheral blood mononuclear cells (PBMCs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Such results indicate that these therapeutic strategies directly decreased IL-4 and IL-17 production by Th2 and Th17 cells, respectively. This finding strongly suggests that both these therapeutic strategies have the potential to break the pathogenesis of allergic asthma at its later stage by the direct inhibitory effect on the production of two cytokines playing a crucial role [ 10 , 11 ] in promoting the development of this disease. In light of the above, one can assume that if the blockade of NF-κB translocation and of RANKL/RANK interaction does not effectively stop the development of allergic asthma at the level of the clonal expansion of CD4 + Teff cells in the MLNs (i.e., in an inductive site of pulmonary immune response), then it can attenuate it at the pulmonary level (i.e., in an effector site of pulmonary immune response) via the inhibitory effect on IL-4- and IL-17 production by lung infiltrating Th2 and Th17 cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such results indicate that these therapeutic strategies directly decreased IL-4 and IL-17 production by Th2 and Th17 cells, respectively. This finding strongly suggests that both these therapeutic strategies have the potential to break the pathogenesis of allergic asthma at its later stage by the direct inhibitory effect on the production of two cytokines playing a crucial role [ 10 , 11 ] in promoting the development of this disease. In light of the above, one can assume that if the blockade of NF-κB translocation and of RANKL/RANK interaction does not effectively stop the development of allergic asthma at the level of the clonal expansion of CD4 + Teff cells in the MLNs (i.e., in an inductive site of pulmonary immune response), then it can attenuate it at the pulmonary level (i.e., in an effector site of pulmonary immune response) via the inhibitory effect on IL-4- and IL-17 production by lung infiltrating Th2 and Th17 cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells also play a key role in promoting and maintaining airway inflammation. IL-17 is considered to be the main proinflammatory cytokine involved in the pathogenesis of allergic asthma; it plays a critical role in neutrophil and eosinophil recruitment to the lungs [ 11 ]. Although the central role in the pathogenesis of asthma is played by CD4 + T cells, numerous studies prove that CD8 + T cells also participate in the development of the disease [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a chronic in ammatory disorder of the airways with a change in the T helper (Th) 1/Th2 balance and an imbalance in the ratio between regulatory T cells (Chan et al 2016). It has been reported that while Th2 cells cytokines cause in ammatory responses in the asthmatic airways, Th1 cells can inhibit the development of Th2 cells and reduce the asthma response caused by Th2 (Yang et al 2019). Currently, the protocols used in the treatment of asthma include leukotriene modi ers, glucocorticoids, leukotriene and mast cell stabilizers and besides their serious side effects, they show only symptomatic effects (Salama et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Th17/Treg ratio is positively correlated with the severity of AHR in children with asthma, and is associated with worsening asthma (93,94). Huai Qi Huang (a mixture of Chinese herbs), ligustrazine and oligo-fucoidan can regulate the Th1/Th2 and Treg/Th17 imbalance in asthma, and reduce asthma severity (95)(96)(97). Given the essential role of T cells in asthma, researches that target the imbalance of different subsets of T cells show great potential.…”
Section: The Mechanisms Underlying the Roles Of Il-36 Cytokines In As...mentioning
confidence: 99%